MENINGKATKAN HASIL BELAJAR MELALUI METODE PEMBERIAN TUGAS PADA SISWA KELAS II SEKOLAH DASAR - Desrita Desrita (Jurnal Muara Pendidikan, 2020)
The background of this research was that the classroom atmosphere was very calm, no one responded to the teacher's explanation, even though the teacher had repeatedly given the opportunity to ask questions. The questions given were sufficient, but in the final results of the formative test given by the teacher, the results were still far from what was expected. This study aims to describe the learning achievement of the second semester students of SDN 88 / II Sungai Mengkuang, Bungo Regency, academic year 2016/2017 in Indonesian through the assignment method. This type of research is a classroom action research (PTK) with a qualitative descriptive approach carried out in three cycles. The results showed that the use of the assignment method in class II students can improve student achievement in pre-cycle only 38.7%, 38.7% first cycle, 61.29% cycle, and 87.09% third cycle